Transformasi Fragmen DNA Salmonella Ke Dalam Sel E. coli DH5-α - E.S. Rahayu; A. Pertiwiningrum; R. Indrati; S. Raharjo; S. Rahayu; S. Margino (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1997)
Genomic DNA from Salmonella typhimarium ATCC 14028, cultured in a Luria broth for 24 hr at 37°C, was isolated from the cells using EDTA as a chelating agent and SDS as a detergent and lysing agent. The amount of genomic DNA was then digested with each of three restriction endonucleases, i.e., EcoRI, HindlII, and BamHI for 4 hr at 37Â°C. A plasmid (pUC19) was used as a vector. Prior to use, the pUC19 plasmid was split with one of the three restriction enzymes and dephosphorylated using a bacterial alkaline phosphatase. The genomic DNA was then ligated to the corresponding prediggested plasmid using a ligase at 15°C over night. Transformation of the DNA recombinant into E.coli DH5-a was successfully carried out using a heat shock method as indicated by gel electrophoresis